Vehicle assisted cross-layer handover scheme in NEMO-based VANETs (VANEMO). (1st January 2011) - Prakash, A.; Tripathi, S.; Verma, R.; Tyagi, N.; Tripathi, R.; Naik, K.
The combination of VANET and NEMO is termed as VANEMO. In this paper, we propose the use of ad hoc communications between vehicles in VANEMO to assist seamless NEMO handover in vehicular scenario. Using cross-layer information, a vehicle which is undergoing handover process, can take assistance from other vehicles in the ad hoc region to reduce handover latency as well as to minimise packet loss during handover. Using other vehicle's assistance, a handover vehicle can get the router advertisement of the next access point before actual handover takes place. Thus, it can configure its new care-of-address on the fly, resulting in considerable reduction in handover latency. At the same time, another vehicle in the ad hoc region may assist in receiving packets destined for handover vehicle, resulting in minimisation of packet loss during handover period. The main contribution of this paper is to optimise handover latency and minimise packet loss based on the uses of mixed ad hoc and infrastructure communications, thus enabling vehicle to infrastructure communications to be improved. The proposed solution is characterised and evaluated through extensive simulation, showing that it provides an efficient handover in vehicular communications.